Breastfeeding support during the Covid-19 pandemic in England: analysis of a national survey - Quigley, MA; Harrison, S; Levene, I; Buchanan, P; McLeish, J; Alderdice, F (BioMed Central, 2024)
Background: Breastfeeding support interventions are associated with longer breastfeeding duration. Contemporary nationally representative data on breastfeeding support as reported by women in England is lacking. Using English national maternity survey data, we describe sources and modes of breastfeeding support as reported by women who gave birth in 2020; sources of support are compared with earlier maternity surveys (2014, 2016, 2018). We also explore the characteristics associated with source/mode of support in 2020 (n = 4,611). Methods: Women who breastfed were asked about sources of breastfeeding support (midwife; other health professional; other formal breastfeeding support such as breastfeeding specialist, breastfeeding support group, peer supporter; and partner/friend/relative), how this help was given and whether they would have liked more help from a health professional with breastfeeding. Adjusted risk ratios (aRR) for the association between sociodemographic and pregnancy-related variables and each source/mode of support were estimated using modified Poisson regression. Results: From 2014 to 2020 support from midwives and other health professionals declined (from 84.0% to 64.7%, and 61.6% to 15.5% respectively) whereas other formal breastfeeding support and informal support from partners/friends/relatives remained constant at 27–31% and 34–38% respectively. The proportion of women who wanted more help with breastfeeding increased from 30% in 2014–2018 to 46% in 2020. In 2020, women most likely to want more help with breastfeeding were nulliparous (aRR = 1.64, 95%CI:1.50–1.79), younger (aRR = 1.21, 95%CI:1.03–1.42) and of Pakistani ethnicity (aRR = 1.30, 95%CI:1.06–1.60). Receiving breastfeeding support over the phone (35%) was more common than via video call (13%) or text message (5%); these percentages varied according to socio-demographic and pregnancy-related factors. Conclusions: Breastfeeding support has declined in recent years, and did not meet the needs of many women during the pandemic. Planning for a future emergency should include adequate provision of breastfeeding support particularly if staff are redeployed into other roles. The characteristics associated with support can inform service planning and delivery. Future research should use these factors to develop novel ideas for intervention, such as directly targeting partners or other informal networks with educational or psychosocial interventions.